Peran Promosi Media Sosial Terhadap Penjualan Produk Ayunda Florigift Tebing Tinggi - Rumiris Siahaan; Eka Juli Nurhalizah; Gustiana Dewi; Intan Larasati; Anisa Fadhila; Lusi Rahmawati; Risa Dwi Diyanti; Rakhmawati Purba (Community Service Progress, 2026)
This study aims to determine the role of promotion conducted through social media in increasing sales at Ayunda Florigift SMEs. In today's digital era, social media has become one of the most widely used promotional tools by businesses, especially SMEs with limited marketing budgets. The research method used is qualitative descriptive, with data collection techniques including observation, interviews, and documentation. The results of the study indicate that promotions conducted through social media, particularly Instagram and WhatsApp Business, have a positive impact on sales growth. Promotional activities such as posting visually appealing product images, using persuasive captions, offering regular promotions, and responding quickly to consumers can increase brand awareness, purchasing interest, and customer engagement. Effective promotions through social media have been proven to drive purchasing decisions and contribute to an increase in the number of transactions.